2002
DOI: 10.1097/00000374-200201000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Implicit and Explicit Alcohol-Related Cognitions

Abstract: This article presents the proceedings of a symposium at the 2001 RSA Meeting in Montreal, Canada organized by Reinout W. Wiers and Alan W. Stacy. The purpose of the symposium was to present recent applications of implicit cognitive processing theory to alcohol research. Basic cognitive research has demonstrated that implicit cognition influences memory and behavior without explicit recall or introspection. The presentations from this symposium show that implicit cognition approaches yield new insights into und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
40
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 32 publications
2
40
0
1
Order By: Relevance
“…With these traditional measures, scores obtained are often negative, independently of the subjects' smoking or alcohol dependence (Wiers & de Jong, 2006). These negative scores could therefore be interpreted as a manifestation of negative attitude toward these objects.…”
Section: Mots-clefs: Sc-iat-p Papier Crayon; Attitude Implicite; Tabamentioning
confidence: 99%
See 1 more Smart Citation
“…With these traditional measures, scores obtained are often negative, independently of the subjects' smoking or alcohol dependence (Wiers & de Jong, 2006). These negative scores could therefore be interpreted as a manifestation of negative attitude toward these objects.…”
Section: Mots-clefs: Sc-iat-p Papier Crayon; Attitude Implicite; Tabamentioning
confidence: 99%
“…Thus, according to Olson and Fazio (2004), the test not only measures personal attitude: the valence of the attitude is contaminated by the "general opinion" (Wiers & de Jong, 2006) to the attitudinal object. For example, the negative score for the tobacco object can be interpreted as reflecting a collectively shared negative evaluation of tobacco.…”
Section: Mots-clefs: Sc-iat-p Papier Crayon; Attitude Implicite; Tabamentioning
confidence: 99%
“…It has been suggested that the onset of alcohol would depend on the explicit process while the implicit process would play a more important role in the continued use ( Given that the number and variety of publications in the area is overwhelming, the purpose of this article is to review the scientific production on the topic by means of a bibliometric and content analysis of the empirical studies published up to May, 2013. Although there are interesting review papers about IAC, they are confined to a specific aspect of IAC, such as the indirect methods to asses IAC (Reich, Below & Goldman, 2010, Wiers & de Jong, 2006, the relationship between IAC and behavior (Rooke, Hine & Thorsteinsson, 2008), or the ways to modify IAC (Wiers, de Jong, Havermans & Jelicic, 2004). However, the present article aims to provide a global vision of the investigations about 705 Trends in the study of implicit alcohol related cognition / Biscarra, Conde, Carcelén IAC.…”
mentioning
confidence: 99%
“…However, as Wiers & de Jong (2006) postulate, a central paradox of addiction is that addicted people continue consuming despite knowing the associated risks. In order to explain these irrational behaviors, during the 70s and 80s, several new theories proposed the existence of two processes underlying behavior: an explicit and controlled process and an implicit and automatic process (Chaiken, 1980;Devine, 1989;Fazio, Sanbonmatsu, Powell & Kardes, 1986;Wason & Evans, 1975).…”
mentioning
confidence: 99%
See 1 more Smart Citation